Schumpeterian analysis of economic catch-up : knowledge, path-creation, and the middle-income trap - Lee, Keun, 1960- (Cambridge : Cambridge University Press, 2013)
One of the puzzles about why some countries have stronger economic growth than others revolves around the so-called 'middle-income trap', the situation in which a country that has grown strongly gets stuck at a certain level. In this book, Keun Lee explores the reasons why examples of successful catching-up are limited and in particular, why the Asian economies, including China, have managed to move, or are moving, beyond middle-income status but economic growth has stalled in some Latin American countries. This is one of the first studies to demonstrate using patent analysis that the secret lies in innovative systems at the firm, sector and country levels which promote investment in what the author calls 'short-cycle' technologies and thereby create a new path different from that of forerunning countries. With its comprehensive policy framework for development as well as useful quantitative methods, this is essential reading for academic researchers and practitioners.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Schumpeter, Joseph A., -- 1883-1950.; Technological innovations -- Developing countries; Economic development -- Developing countries